PENDAMPINGAN DAN INOVASI PRODUKSI MINUMAN HERBAL PENJAGA IMUNITAS KHAS NGAWI JAWA TIMUR - Novia Enka Purnamasari; Yudha Nurdian (Politeknik Negeri Sriwijaya, 2020)
The spread of Covid-19 has widened to have an impact in rural areas, one of which is Geneng village, Geneng District, Ngawi Regency. Many of the people of Geneng village are affected in various areas of their livelihood, including as employees of a textile factory, bridal makeup, school canteen keepers, building contractors (migrants) so that the village community becomes unemployed. The condition of the spread of the Covid-19 pandemic is also very worrying in the health sector, the need for all elements to maintain body immunity. The Back To Villange Real Work Lecture Program at the University of Jember provides concrete evidence of providing entrepreneurial empowerment for people affected by Covid-19 with the herbal beverage entrepreneurial innovation work program